Effect of octyl salicylate with respect to the physical appearance of mono/di capric and caprylic fatty acids formulations - Abd Gani, Siti Salwa; Lane, Majella E.; Ramli, Rabiatul Adawiah; Basri, Mahiran; Mohd Mokhtar, Nor Fadzillah (OMICS International, 2016)
In this study, the behavior of the caprylic and capric acids formulations containing octyl salicylate were investigated. The formulations were formulated using homogenization proses. The particle size, flow behavior, microscopic view and absorbance of the formulations were investigated. Particle sizes of the formulations were found in range 352.7 nm - 704.2 nm. The viscosity of the formulations changed as the shear rate was varied and could be classified as non-Newtonian fluids. The viscosity decreases when the fluid undergoes longer shear stress with time. The formulations containing octyl salicylate shows higher absorbance as compared to the formulations without octyl salicylate. The addition of octyl salicylate affected the system in terms of behavior, appearance and stability.